1986
DOI: 10.1136/pgmj.62.725.197
|View full text |Cite
|
Sign up to set email alerts
|

Focal myositis and elevated creatine kinase levels in a patient with phaeochromocytoma

Abstract: Summary A case of phaeochromocytoma with marked transient elevation of creatine kinase levels is presented. No obvious cause for the elevation was found in life, but on autopsy a non-specific focal myositis was discovered. Possible reasons for the raised creatine kinase levels and focal myositis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Recently, some case reports showed that pheochromocytoma could induce rhabdomyolysis and acute renal failure with increased creatine kinase levels but had not performed biopsy 10, 11, 12. There is just evidence in the literature of histologically proven focal myositis with degeneration of skeletal muscle fibers, increased sarcolemmal nuclei, and giant cells in a patient with a large pheochromocytoma at autopsy 13. In our case, we performed a biopsy of the patient's bicep muscle, and electron microscopic examination revealed deranged myofibrils, atrophy, increased mitochondrial number, as well as damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some case reports showed that pheochromocytoma could induce rhabdomyolysis and acute renal failure with increased creatine kinase levels but had not performed biopsy 10, 11, 12. There is just evidence in the literature of histologically proven focal myositis with degeneration of skeletal muscle fibers, increased sarcolemmal nuclei, and giant cells in a patient with a large pheochromocytoma at autopsy 13. In our case, we performed a biopsy of the patient's bicep muscle, and electron microscopic examination revealed deranged myofibrils, atrophy, increased mitochondrial number, as well as damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pheochromocytoma can cause muscle damage; there is evidence in the literature of histologically proven focal myositis with degeneration of skeletal muscle fibers, increased sarcolemmal nuclei, and giant cells in a patient with a large pheochromocytoma at autopsy. 13 Making a diagnosis of pheochromocytoma depends on demonstrating excessive production of catecholamines (total and fractionated metanephrines, vanillylmandelic acid) with tumor localization. Although recent studies suggest that measurement of plasma free metanephrines is a superior test for confirming the diagnosis, a high urinary fractionated metanephrine level was detected at our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pheochromocytoma, high circulating levels of catecholamines, especially of the alpha-agonist norepinephrine, would be expected to cause vasoconstriction and skeletal muscle ischemia. In addition, skeletal muscle is innervated by adrenergic receptors [17], and elevated levels of catecholamines could potentially cause excessive and repetitive stimulation, leading to muscle fatigue and injury.…”
Section: Discussionmentioning
confidence: 99%
“…These include saralasin, sulpiride, droperidol, metoclopramide, ergotamine, caffeine, nimesulide, opiates, histamines, and glucagon among others [5][6][7][8][9]. Our search of the literature found six reports of steroid-induced pheochromocytoma crisis [10][11][12][13][14][15] and only a few reports of rhabdomyolysis in pheochromocytoma patients [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%